Recurrent spontaneous pneumothorax under nintedanib treatment in ınterstitial lung disease associated with systemic sclerosis - Şenel, Abdurrahman Soner; Kahraman Denizhan, Tuğba; Kızıltepe, Melih; Oğuz Kökoğlu, Emel; Tutar, Nuri (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Interstitial lung disease (ILD) is a common complication that can develop during the course of systemic sclerosis (SSc). Nindetanib is an antifibrotic drug approved for the treatment of systemic sclerosis-associated interstitial lung disease. Although there is an insufficient data on the development of pneumothorax, the safety of Nintedanib treatment is also uncertain. We observed recurrent resistant pneumothorax under nintedanib treatment in a patient with systemic sclerosis-associated interstitial lung disease. Nintedanib use may increase the risk of developing refractory pneumothorax. Ssc patients who are started on nintedanib should be followed carefully for pneumothorax.